Multi-phase modelling of electrochemical rehabilitation for ASR and chloride affected concrete composites. (1st January 2019) - Mao, Li-xuan; Hu, Zhi; Xia, Jin; Feng, Gan-lin; Azim, Iftikhar; Yang, Jian; Liu, Qing-feng
Abstract: Reinforced concrete structures experience severe durability degradation when subjected to alkali–silica reaction (ASR) and chloride attack. A special electrochemical rehabilitation treatment, containing lithium compound anolyte, has been developed to drive lithium ions into concrete composites and remove chlorides simultaneously, for mitigating both the ASR-induced cracks and the chloride-induced reinforcing steel-bar/fiber corrosion. In this study, the efficiency of the impregnation of lithium ions and the removal of chloride ions through a specific electrochemical treatment is numerically evaluated, which results into the distribution profiles of all typical ionic species. A heterogeneous numerical model, which treats concrete as a three-phase composite, is presented to examine the response of inner structures, especially the interaction between active aggregates and lithium ions that are supposed to mitigate ASR. The ionic interaction between different species, binding and the electrochemical reaction at electrodes are also considered. Through a detailed modelling of multi-phase and multi-species, a systemic parametric analysis based on a series of significant factors during electrochemical treatment (e.g., current density, treatment time, temperature, cathode position and concentration of lithium solution) reveals some important tendencies of ionic electromigration in concrete structures, which are supposed to guide the field applications.